THE EFFECT OF PROFITABILITY AND RISK MANAGEMENT ON WORKING CAPITAL MANAGEMENT - Mudji Utami (Journal of Management and Business, 2011)
This study aims to examine the impact of working capital management on profitability and risks of business companies. Furthermore, this study also examines what are the differences of working capital management industries in the manufacturing sector. Some researchers proved that influence of working capital management on profitability (Rahemanand Nasr 2007; Marc Deloof, 2003 and Hadori, 2005). In addition, Gitman (2009) also states that working capital management has an impact on firm profitability and risk. Business risk of each industry is different, thus working capital management will differ among industries. This study used data from 2001 until 2007 at the manufacturing sector firms which have coherent of annually financial statements during the study period and have been audited. In order to test the hypothesis, this study used regression analysis and analysis of variance. The research proves that working capital management affects profitability and risk of firm manufacturing sector during the period 2001-2007. Moreover, it also proves that there is a difference among working capital management industries in the manufacturing sector.